Telesne značilnosti in gibalne sposobnosti učencev košarkarsko najuspešnejših osnovnih šol v tekmovanju starejših učencev - Sirnik, Matic (Šport (Ljubljana), 2021)
Basketball performance is influenced by many factors, including basketball skills and experience, situational thinking, favourable body measurements, and well-developed motor skills. Some factors can be perfected and measured in the training process to check the level of development. Various measurement tasks are used worldwide for measurement, some of which are similar to the individual tasks of the Sports Educational Chart (ŠVK). In the ŠVK test battery, two measures of physical characteristics and four motor tasks are particularly interesting for basketball. We examined the results of these tests at the four most successful basketball schools and compared them to the Slovenian population and within schools between generations based on basketball success. The results show that the more successful basketball generations are taller than their peers, and their above-average results are also evident in general endurance, explosive leg strength, sprint speed, and core strength. Based on the results of the selected tasks, we can assume that favourable physical dimensions and above-average developed motor skills in combination with other factors contribute to success in basketball.
Keywords: basketball; children; gibalne sposobnosti; košarka; motor skills; otroci; physical characteristics; sport; Sport Educational Chart; šport; športnovzgojni karton; telesne značilnosti